PENINGKATAN KAPASITAS DAN KINERJA SIMPANG BERSINYAL DALAM PERENCANAAN FLYOVER SIMPANG TANJUNG API-API – PALEMBANG - Djaenudin Hadiyana (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
In general the intersection is vulnerable to jamming because of frequent conflicts between vehicles, the second meeting of the conflict is the path of the vehicle. One of Tanjung Api-Api KM 9 Palembang is one intersection signals that are pretty solid. Research needs to be done for it to provide. The capacity of the junction (C) and volume (V) vehicles that operate on the junction parameters to find out the level of service the junction. Geometric intersection data, the volume of the vehicle, the condition of the city and the junction is analyzed using Manual Indonesia road capacity (MKJI) 1997 and Bina Marga (BM/2013) to get the capacity of the junction and the junction service levels from a year 2016-2021. The results of the analysis of the capacity of Tanjung Api-Api KM 9 Palembang at peak morning is 3365 smp/hour, at peak lunch is 3304 smp/hour and at the peak of the afternoon was 3196 smp/hour. While the road level of service (Level of Service/LOS) on Tanjung Api Api KM 9 Palembang at peak hours in the morning at Jln. Kol. H. Burlian with level of service